Systematic Analysis of Language Transcripts Solutions: A Tutorial - (:unkn) unknown (My University, 2023)
Purpose: In the early 1980s, researchers and speech-language pathologists (SLPs) collaborated to develop the Systematic Analysis of Language Transcripts (SALT). Research and development over the ensuing decades has culminated into SALT Solutions, a set of tools to assist SLPs to efficiently complete language sample analysis (LSA) with their clients. In this tutorial, we describe how SALT can assist with the accurate identification of children with language disorders and provide a rich description of children's functional language use. After summarizing the multiple elicitation methods developed by the SALT team, we provide case studies, showing how to select an elicitation method that aligns with a child's characteristics. We then summarize major considerations when transcribing, analyzing, and interpreting language samples with SALT. We revisit our case studies to illustrate how SALT adds value to the comprehensive assessment of language in children. Conclusions: LSA is a powerful assessment tool for children suspected of having language disorders. The SALT suite of solutions provides a toolkit to assist SLPs with their comprehensive language assessments.